2020
DOI: 10.1016/j.molcel.2019.10.016
|View full text |Cite
|
Sign up to set email alerts
|

An mTORC1-to-CDK1 Switch Maintains Autophagy Suppression during Mitosis

Abstract: Highlights d Autophagy initiation is repressed during mitosis, even during nutrient deprivation d RAPTOR phosphorylation in mitosis prevents mTORC1 localization to lysosomes d mTORC1 is inhibited during mitosis d CDK1 phosphorylates autophagy regulators at mTORC1 sites to repress autophagy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 76 publications
4
112
1
Order By: Relevance
“…Although it is well known that mTOR and AMPK phosphorylate ULK1/ATG13 in asynchronous cells [18,19], we found that mTOR or AMPK inhibition did not affect ULK1/ATG13 band shift in mitosis. In fact, it should be mentioned that although our preprint manuscript (BioRxiv on May 2019) was in revision in this journal, Odle and colleagues published a work also showing that CDK1 could phosphorylate ULK1 and ATG13 in mitosis [63]. They performed in vitro assays and identified phosphorylation sites using a short truncation of ULK1 or ATG13 and proposed that CDK1 could substitute mTOR to phosphorylate ULK1/ATG13.…”
Section: Ulk1/atg13 Phosphorylation By Mtor Ampk and Cdk1mentioning
confidence: 99%
“…Although it is well known that mTOR and AMPK phosphorylate ULK1/ATG13 in asynchronous cells [18,19], we found that mTOR or AMPK inhibition did not affect ULK1/ATG13 band shift in mitosis. In fact, it should be mentioned that although our preprint manuscript (BioRxiv on May 2019) was in revision in this journal, Odle and colleagues published a work also showing that CDK1 could phosphorylate ULK1 and ATG13 in mitosis [63]. They performed in vitro assays and identified phosphorylation sites using a short truncation of ULK1 or ATG13 and proposed that CDK1 could substitute mTOR to phosphorylate ULK1/ATG13.…”
Section: Ulk1/atg13 Phosphorylation By Mtor Ampk and Cdk1mentioning
confidence: 99%
“…Two papers (one by Li and colleagues in this issue and another recently published in Molecular Cell by Odle and colleagues) reveal that CDK1 phosphorylates the autophagy machinery [26,27] (Fig 1). In these works, both groups observe up-shifted bands of ULK1 and ATG13 in mitotic cell lysates.…”
Section: Phosphorylation Of the Atg Proteins During Mitosismentioning
confidence: 94%
“…These Golgi-derived autophagosomes promote clearance of cytosolic DNA and incoming DNA viruses like HSV1 [80]. Although mitotic cells appear to avoid classical induction of autophagy via CDK1 phosphorylation of ATG13, ULK1, and ATG14 [81,82], downstream STING-dependent activation of autophagophore formation/elongation via WIPI2/ATG5 during open mitosis could be deleterious to daughter cell survival [83,84].…”
Section: Cgas and Sting Are Non-responsive During Mitosismentioning
confidence: 99%